2023
DOI: 10.3390/bs13030275
|View full text |Cite
|
Sign up to set email alerts
|

Battling Unawareness of One’s Test Performance: Do Practice, Self-Efficacy, and Emotional Intelligence Matter?

Abstract: The “Dunning–Kruger effect” refers to the tendency of poor performers to overestimate test outcomes. Although a widespread phenomenon, questions exist regarding its source and sensitivity to countermeasures. The present field study aimed to (a) examine whether practice with tests used in previous classes can enhance students’ ability to estimate test outcomes, (b) determine the main source of the effect (i.e., is it unawareness of one’s readiness or wishful thinking?), and (c) assess the extent to which partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…However, the steepest decline was yielded by deficient performers. These findings, which replicate those of Pilotti et al (2021 , 2023c) , suggest that learners’ metacognitive experiences before and after the exam are different. Before the exam, the key sources of estimates are study activities and scant information about the format and content of the exam gathered from the instructor and past students.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, the steepest decline was yielded by deficient performers. These findings, which replicate those of Pilotti et al (2021 , 2023c) , suggest that learners’ metacognitive experiences before and after the exam are different. Before the exam, the key sources of estimates are study activities and scant information about the format and content of the exam gathered from the instructor and past students.…”
Section: Discussionsupporting
confidence: 69%
“… Miller and Geraci (2011a) also found that low-performing students make grade predictions with less confidence than high-performing students. Svanum and Bigatti (2006) and Pilotti et al (2023c) argued that for students whose performance is less than desirable, optimistic predictions may be the expression of wishful thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation